1994
DOI: 10.1002/1097-0142(19941101)74:9<2497::aid-cncr2820740917>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of squamous cell carcinoma antigen and tumor size are useful to identify preoperatively patients at high risk of cervical cancer

Abstract: Background. The benefit of postoperative adjuvant therapy for patients with cervical cancer is uncertain, and moreover, may increase morbidity. In this study, patient age, clinical stage of the cancer, tumor size, and levels of serum squamous cell carcinoma cell antigen and carcinoembryonic antigen were studied in patients with Stage Ib and IIa squamous cell carcinoma of the uterine cervix to determine if these parameters can be used, be fore the surgical intervention, to distinguish patients who require posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…It is still debated whether pre-treatment SCC assay may represent a prognostic variable, useful for selecting a group of high-risk patients who need more aggressive therapy [14,38,107]. Serum SCC reflects the response to treatment, and rising antigen levels often precede the clinical detection of recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is still debated whether pre-treatment SCC assay may represent a prognostic variable, useful for selecting a group of high-risk patients who need more aggressive therapy [14,38,107]. Serum SCC reflects the response to treatment, and rising antigen levels often precede the clinical detection of recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…The histological classification was defined according to the World Health Organization classification. The cervical tumour volume of surgical specimen was calculated using the formula: p/6 Â (R 1 Â R 2 Â R 3 ) (Chou et al, 1994). Preoperative serum levels of tumour markers were available.…”
Section: Patient Populationmentioning
confidence: 94%
“…During the early treatment of cervical cancer, the levels of SCC have been shown to be related to the stage of the disease, size of the tumor and depth of the stromal invasion [26]. Earlier studies have shown that elevated levels of SCC have predictive value for prognosis [27] and they indicated that this SCC-Ag may also be used to show the response of therapy [28] and also used in the follow-up examination of cervical cancer patients. Increased serum SCC was shown to precede the clinical detection of recurrence of the disease [29].…”
Section: Squamous Cell Carcinoma Antigen (Scc-ag)mentioning
confidence: 99%